Respuesta :
Answer:
y = 4 - x
Step-by-step explanation:
Given,
The speed of David's boat = 6 miles per hour,
Speed of stream = 2 miles per hour,
So, the speed of boat in upstream = Speed of boat - Speed of stream
= 6 - 2
= 4 miles per hour,
Now, this speed is decreasing at the rate of 1 miles per hour,
So, the total decreased speed in x hours = x miles per hour,
Hence, the final speed of boat after x hours = ( 4 - x ) miles per hour,
If y represents the final speed ( miles per hour ) of boat after x hours ,
⇒ y = 4 - x
Which is the required equation.